The Impact of Clinical Teaching Behavior on Learning Experience of Nursing Students - Mariano, Maria E. M.; Al-Jamea, Lamiaa H.; Al-Ansari, Rehab; Aldossary, Nasrah; Shamrani, Abeer Al; Quiambao, Jenifer V.; Balilla, Jeffhraim; Woodman, Alexander (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Clinical education is the cornerstone of nursing education and an important aspect of the nursing curriculum. The perspective of nursing students and clinical teachers can have a significant impact on the curriculum and knowledge delivery. This research aimed to investigate the influence and effect of the teaching methods utilized by clinical teachers on the training of Saudi nursing students.A descriptive cross-sectional quantitative study was conducted among n = 135 nursing students at different levels of education. Nursing Clinical Teacher Effectiveness Inventory was administered and analyzed to address the aim.Respondents rated Teaching Ability as the most effective clinical teaching behavior (mean [M] = 3.98, standard deviation [SD] = 0.84), followed by Nursing Competence (M = 3.92, SD = 0.81). Both Interpersonal Relations and Personality were equally rated at M = 3.88, while Evaluation received the lowest overall mean (M = 3.75, SD = 0.98). Multivariate analysis of variance results indicated significant differences in students' perceptions across academic levels (Pillai test = 0.51, F = 3.79, p < 0.001).These findings highlight the importance of tailoring clinical teaching strategies based on program level. The Bachelor of Science in Nursing (BSN4) cohort consistently rated all teaching dimensions more favorably, suggesting higher satisfaction or more developed expectations among students in the later stages of their program. Conversely, lower ratings from Bridging 2 (BRID) students indicate a potential gap in their clinical learning experience. These disparities emphasize the need for a program-level-responsive approach to clinical teaching—strengthening underperforming categories like Evaluation, while reinforcing effective practices in cohorts with positive perceptions.
Keywords: nursing education; clinical teacher; students; perspectives; behavior